Spatio-Temporal Analysis of Land Use Change in the Johor River Basin, Malaysia - Yi, Lin Tew; Mou, Leong Tan (European Publisher, 2019)
Land use land cover (LULC) change analysis is one of the major studies around the world. Understanding the spatial and temporal changes in the historical LULC pattern is critical for impact assessment, town planning, and future LULC simulation. Johor, situated in the southern Peninsular Malaysia, is one of the most developed states in Malaysia. Johor River Basin (JRB) is the main springhead for Johor and Singapore. However, research on LULC analysis of JRB is still rarely reported. This study aims to understand the spatio-temporal changes of LULC in JRB between 1984 and 2015. The study is divided into two main parts: (1) to identify the LULC types with rapidly changes; and (2) to compute the rate of LULC changes. Three land use maps of 1984, 2002 and 2015 were collected from the PLANMalaysia agency. The results show that JRB experienced rapid growth in oil palm where the estate area expanded 47.98% from 1984 to 2015. In contrast, the forest area was decreased by 7.74% between 1984 and 2015, particularly in the southern part of JRB. Meanwhile, a significant increasing trend was found for water bodies in the northern part of the basin. This is mainly due to the construction of Linggiu Reservoir for supplying fresh water to Singapore in the early 1990s. LULC changes should be monitored and well managed to maintain the sustainability of life and water resources, by incorporating it into the hydrological model to study the future water resources of the basin.